Food Security and Food Control Strategies for The Benefit of The Indonesian People - Muliyarti, Elfrida; Longgok, Yogiardus Anugera; Cembes, Fabiola Cindi; Gunawan, Cakti Indra (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2024)
Food security is very important for Indonesia, considering the large and growing population. This study aims to analyze food control strategies for food security in Indonesia using comparative descriptive analysis and literature studies. The results show that the implementation of food security strategies in Indonesia has not been optimal, with challenges such as agricultural sector liberalization, inadequate infrastructure, and stalled programs. This research highlights the importance of government intervention, economic efficiency, equitable control of production factors, and partnerships in creating sustainable food security for the benefit of the Indonesian people. Effective strategies to increase food security include food SOE holding, commodity pricing, cooperative development, and agrarian reform.